2016
DOI: 10.18415/ijmmu.v3i2.46
|View full text |Cite
|
Sign up to set email alerts
|

Blended Learning in the Vocational Education and Training System in Tanzania: Understanding Vocational Educators’ Perceptions

Abstract: In a constructivist world of teaching and learning, opportunities to acquire and develop the knowledge and practical skills necessary to design, establish, and deploy blended learning in vocational education and training (VET) programs delivery is a labour-market-driven. The paper examines VET educator"s pleas about the need for the design, adoption and deployment of blended learning in VET programs delivery in Tanzania. A single case study design with an in-depth interview and focus group discussion was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The results obtained are considered that Blended learning is an activity that takes place in two different areas, namely in person and online. Locally designed mixed learning should fit the environment for both teachers and students [30].…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained are considered that Blended learning is an activity that takes place in two different areas, namely in person and online. Locally designed mixed learning should fit the environment for both teachers and students [30].…”
Section: Resultsmentioning
confidence: 99%
“…The study showed that T&VSS students had higher support of classroom environment compared with the students from RSS and NSS. These findings were supported by the study by Machumu, Zhu and Sesabo (2016) who asserted that soft skills are applied at a higher level in T&VSS when students are in the classroom, workshop, and when students attend extra-curricular activities. Support of the students in T&VSS is inseparable from the support of teachers.…”
Section: Discussionmentioning
confidence: 56%
“…Emphasizing good relations with teachers is important so that students' commitment to learning are always high. Therefore, locally designed blended learning should be relevant to the environment for both students and teachers (Machumu, Zhu and Sesabo, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…(cf. blended learning environment-BLE) (Machumu, Zhu & Sesabo, 2016;Ocak & Akçayır 2013;Radosavlevikj, 2016). In this direction, other researchers have studied similar effects and its impact on new methodological processes of education (Eryilmaz, 2015;Graham & Dziuban, 2015) According to these last trends in education and the extensive use of technology in every aspect of society, education cannot be left behind evolution and it must adapt itself.…”
Section: Resultsmentioning
confidence: 99%